2022
DOI: 10.1177/10711007221106472
|View full text |Cite
|
Sign up to set email alerts
|

Pain Catastrophizing Scale Associated With Other Patient-Reported Outcome Measures in Plantar Fasciitis and Chronic Ankle Instability Patients

Abstract: Background: The Pain Catastrophizing Scale (PCS) is a measure of how patients emotionally respond to pain. It is composed of 3 subscales—rumination, magnification, and helplessness—which address intrusive thoughts of pain, expectations of negative outcomes, and inability to cope with pain. Our purpose is to compare baseline PCS scores with other baseline patient-reported outcome measures (PROMs) in patients with plantar fasciitis (PF) or chronic ankle instability (CAI). Methods: We retrospectively reviewed 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…in patients with plantar fasciitis (PF) and chronic ankle instability (CAI). 6 The PCS is a 13-point scale that has been proven to be a reliable and valid tool to test catastrophizing and is a self-reported questionnaire built around Active smokers were rare (6%), although diabetes was more frequent (14%). The mean followup was six months.…”
Section: Pain Catastrophizing: the Same As Pain Forecasting?mentioning
confidence: 99%
See 1 more Smart Citation
“…in patients with plantar fasciitis (PF) and chronic ankle instability (CAI). 6 The PCS is a 13-point scale that has been proven to be a reliable and valid tool to test catastrophizing and is a self-reported questionnaire built around Active smokers were rare (6%), although diabetes was more frequent (14%). The mean followup was six months.…”
Section: Pain Catastrophizing: the Same As Pain Forecasting?mentioning
confidence: 99%
“…In this interesting report from Charleston (South Carolina, USA) , the authors reported on the relationship between the Pain Catastrophizing Scale (PCS) and other patient-reported outcome measures (PROMs) in patients with plantar fasciitis (PF) and chronic ankle instability (CAI). 6 The PCS is a 13-point scale that has been proven to be a reliable and valid tool to test catastrophizing and is a self-reported questionnaire built around three domains: rumination (to address negative intrusive thoughts of pain); magnification (expectation of negative outcomes); and helplessness-inability to cope with pain. The authors compared baseline PCS scores with baseline visual analogue scale (VAS), Pain Disability Index, 12-Item Short-Form Health Survey, and eight-item Somatic Symptom Scale.…”
Section: Pain Catastrophizing: the Same As Pain Forecasting?mentioning
confidence: 99%